Be and Zn behavior during anatectic formation of early pegmatoid melts in variscan terrains: an example from the Arga pegmatite field, northern Portugal - Dias, Patrícia Sofia Alves (2013)
Publicado em "PEG 2013 : Contributions to The 6th International Symposium on Granitic Pegmatites"